Regulating Chondrogenesis of Human Mesenchymal Stromal Cells with a Retinoic Acid Receptor-Beta Inhibitor: Differential Sensitivity of Chondral Versus Osteochondral Development - Solvig Diederichs; Kerstin Zachert; Patric Raiss; Wiltrud Richter (Cellular Physiology and Biochemistry, 2014)
Aim: Main objective was to investigate whether the synthetic retinoic acid receptor (RAR)-β antagonist LE135 is able to drive in vitro chondrogenesis of human mesenchymal stromal cells (MSCs) or improve differentiation by suppressing hypertrophic chondrocyte development. Methods: Chondrogenesis of human bone marrow and adipose tissue-derived MSCs was induced in micromass pellet culture for six weeks. Effects of LE135 alone and in combinatorial treatment with TGF-β on deposition of cartilaginous matrix including collagen type II and glycosaminoglycans, on deposition of non-hyaline cartilage collagens type I and X, and on hypertrophy markers including alkaline phosphatase (ALP), indian hedghehog (IHH) and matrix metalloproteinase (MMP)-13 were assessed. Results: LE135 was no inducer of chondrogenesis and failed to stimulate deposition of collagen type II and glycosaminoglycans. Moreover, addition of LE135 to TGF-β-treated pellets inhibited cartilaginous matrix deposition and gene expression of COL2A1. In contrast, non-hyaline cartilage collagens were less sensitive to LE135 and hypertrophy markers remained unaffected. Conclusion: This demonstrates a differential sensitivity of chondral versus endochondral differentiation pathways to RARβ signaling; however, opposite to the desired direction. The relevance of trans-activating versus trans-repressing RAR signaling, including effects on activator protein (AP)-1 is discussed and implications for overcoming current limits of hMSC chondrogenesis are considered.